Spectrophotometric Determination of Cefixime by Oxidative Coupling Reaction with 4-Aminophenol in the Presence of Potassium periodate - Ali Ibraheem Khaleel; Heba Ibrahim Abdulla (Tikrit Journal of Pure Science, 2023)
This work involves a new simple, rapid and sensitive spectrophotometric method for the determination of Cefixem. The method based on the oxidative coupling reaction between Cefixime and 4-Aminophenol using Potassium periodate as oxidizing agent to form a violet color water soluble product that has a maximum absorption at 537 nm. The optimum conditions were:, pH 6.5, temperature between 25-30 oC. Beer’s law is obeyed in a concentration range of 4 to 30 µg / ml with a molar absorptivity of 6749.75 L.mol-1. cm-1. The relative error was 0.729 to - 0.752 % and a relative standard deviation of 0.556 to 0.861% ,DL= 0.136 µg / ml. The proposed method has been successfully applied to the determination of Cefixime in SAMAXIME Capsules with recovery of not less than 98.1%.